Pharmacogenomics And Hypertension: Current Insights - Oliveira-Paula GH; Pereira SC; Tanus-Santos JE; Lacchini R (Dove Medical Press, 2019)
Gustavo H Oliveira-Paula,1,2 Sherliane C Pereira,2 Jose E Tanus-Santos,2 Riccardo Lacchini3 1Department of Medicine, Division of Cardiology, Wilf Family Cardiovascular Research Institute, Albert Einstein College of Medicine, New York, NY, USA; 2Department of Pharmacology, Ribeirao Preto Medical School, University of Sao Paulo, Ribeirao Preto, SP, Brazil; 3Department of Psychiatric Nursing and Human Sciences, Ribeirao Preto College of Nursing, University of Sao Paulo, Ribeirao Preto, SP, BrazilCorrespondence: Riccardo LacchiniDepartment of Psychiatric Nursing and Human Sciences, Ribeirao Preto College of Nursing, University of Sao Paulo, Av. Bandeirantes, 3900, Ribeirao Preto 14040-902, SP, BrazilTel +55 16 3315-3447Email rlacchini@eerp.usp.brAbstract: Hypertension is a multifactorial disease that affects approximately one billion subjects worldwide and is a major risk factor associated with cardiovascular events, including coronary heart disease and cerebrovascular accidents. Therefore, adequate blood pressure control is important to prevent these events, reducing premature mortality and disability. However, only one third of patients have the effective control of blood pressure, despite several classes of antihypertensive drugs available. These disappointing outcomes may be at least in part explained by interpatient variability in drug response due to genetic polymorphisms. To address the effects of genetic polymorphisms on blood pressure responses to the antihypertensive drug classes, studies have applied candidate genes and genome wide approaches. More recently, a third approach that considers gene-gene interactions has also been applied in hypertension pharmacogenomics. In this article, we carried out a comprehensive review of recent findings on the pharmacogenomics of antihypertensive drugs, including diuretics, β-blockers, angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers, and calcium channel blockers. We also discuss the limitations and inconsistences that have been found in hypertension pharmacogenomics and the challenges to implement this valuable approach in clinical practice.Keywords: antihypertensive therapy, candidate genes, GWAS, gene-gene interactions, hypertension, pharmacogenomics